(untitled) (Research, Society and Development, 2020)
Objective: to analyze milk production and the quality of sleep and anxiety of mothers of newborns admitted to a Neonatal Intensive Care Unit in a maternity hospital. Methodology: this is a quantitative, cross-sectional study. The sample consisted of 107 mothers of newborns admitted to the Neonatal Intensive Care Unit. The Pittsburgh Sleep Quality Index questionnaires and the State-Trait Anxiety Inventory, respectively, were used. For the analysis of the milk volume of mothers who gave birth prematurely, it was considered acceptable in the literature, minimum of 500 ml. Results: the mothers’ average age was 26.,69 ± 6,70, most (74.8%) had a partner as a marital status, had completed high school (45,8%), family income of up to one salary minimum (63,3%) and does not work outside the home (67,3%). The volume of milk extractions performed by mothers ranged from 142,33 ml to 156,77 ml of breast milk for 4 days (p <0,0001). According to the Pittsburg index, the majority (62,7%) had poor sleep quality. As for the classifications of Trait-anxiety and State-anxiety, mothers obtained a moderate level of anxiety, being 57,9% and 67,3% respectively. Conclusion: the milk volume produced and extracted by mothers with newborn children admitted to the Neonatal Intensive Care Unit was low. The women had moderate levels of anxiety and poor sleep quality, interfering with the volume of milk extracted at the Human Milk Collection Station.